Behaviour of triticale cultivars in the state of São Paulo during the period 1985-1987 - Felício, João Carlos; Camargo, Carlos Eduardo de Oliveira; Filho, Antonio Wilson Penteado Ferreira; Castro, Jairo Lopes de (Pesquisa Agropecuaria Brasileira, 2014)
Results of twelve experiments of triticale cultivars carried out at distinct regions of the State of São Paulo, Brazil, in the period 1985-1987, were evaluated to grain yield and resistance to diseases. The correlation between the hectolitric weight (HW) of the grains and the 1000 grain weight (1000 GW) in the trials carried out at Maracaí was studied. The analysis of variance of all the experiments taken together showed highly significant effects for treatments, locations and years. All interactions were significant except for treatment x year. The triticales ITOC 841, ICT 8426, IAC 1, ICT 8433 and ICT 8439 presented the best performance. At Capão Bonito the triticale TCEP 8136 exhibited good productivity. The wheat cultivars IAC 5 and IAC 18 were more productive than the triticale cultivars, only in the experiments carried out at Cruzalia. No significant correlation between HW and 1000 G.W. was found in the considered experiments. The triticale cultivars presented a superior HW in relation to the triticale cultivars; however, the 1000 GW of some triticale cultivars were superior to the wheat IAC S. The occurrence of leaf rust at a superior levels in the wheat IAC 5 in relation to the other wheat and triticale cultivars under study was observed. All genotypes were sensitive to Helmintosporium sp. The triticale cultivar showed lodging resistance in relation to the wheat cultivars.
Keywords: grain yield; hectolitric weight; 1000 grain weight; resistance to disease